The Effect of COVID-19 Pandemic on the Lifestyle Behaviors of Individuals - (:unkn) unknown (SAGE PUBLICATIONS INC, 2021)
The study was planned and administered as a descriptive study to determine how COVID-19 pandemic affected the lifestyle behaviors of individuals. The study was administered from 30 June to 30 September by including 615 adult individuals who had been exposed to the COVID-19 pandemic. Of the healthy lifestyle behaviors scale II, the total mean score was found to be 126.37 +/- 18.58. The health responsibility (p = .032) and nutrition (p = .004) subscale mean scores of women were found to be significantly higher than men, while the spiritual development subscale mean scores of men (p = .047) were found to be significantly higher than that of women. It was found in this study that individuals did not regularly maintain healthy lifestyle behaviors in general during the pandemic period according to the subscales of health responsibility, physical activity, nutrition, spiritual development, interpersonal relationships, and stress management.
Keywords: COVID-19 virus infection; health; life style; pandemics; physical activity